Individual Cognitive Behavioural Therapy for Psychosis (CBTp): A Systematic Review of Qualitative Literature*. Issue 3 (5th December 2013) - Wood, Lisa; Burke, Eilish; Morrison, Anthony
Abstract : Background: Individual Cognitive Behaviour Therapy for psychosis (CBTp) is the first line recommended psychological intervention for adults diagnosed with schizophrenia. However, little is yet known about service users' subjective experiences of CBTp.Aims: This study aimed to conduct a systematic review of qualitative literature to examine service user perspective of CBTp.Method: A thematic synthesis of qualitative studies examining service users' experiences of CBTp was conducted. A total of six studies were included in the analysis.Results: Three superordinate themes were identified: therapeutic alliance; facilitating change; and challenges of applying CBTp.Conclusion : Overall, CBTp is a helpful and acceptable therapeutic approach to service users. Developing a collaborative therapeutic relationship is essential. The applications of CBTp can be problematic and the therapist and client need to work together to overcome these difficulties.